A Systematic Literature Review on Learning Software Application Design Framework for Children with Cerebral Palsy (International Journal of Innovative Computing, 2013)
Cerebral palsy (CP) is a disorder of physical body movement and posture caused by a lesion or injury of the immature brain. It is the primary cause of childhood deformity and the secondary cause of severe mental retardation.  Learning difficulty among children with CP is the biggest problem that requires immediate attention by the application designers and developers.  This paper presents a systematic literature review of learning software application design frameworks between years 2007 and 2012. The aim of this study is to discover the existing learning and other application design frameworks for children with and without CP, their weaknesses and strengths and the type of empirical evaluations performed in this domain.  Our broad search found a number of SLRs corresponding to unique studies.  In this review, we could identify the current research on learning software design frameworks for the children with CP and the learning issues based on the lessons learned from the existing works. Our finding in this SLR shows that most of the developers develop learning software application for children with autism. The studies are becoming popular throughout the years. The current work is part of the ongoing study for developing a new learning application design framework for the children with CP. This effort will help in improving the learning and hence living standard of special children.